Дослідження капсульних нейромереж для розпізнавання природнього мовлення - Петришин, А. Ю. (ХНУРЕ, 2024)
This thesis focuses on evaluating neural network-based models for speech recognition under noisy conditions. It examines the effectiveness of the capsule neural network across various types and intensities of noise. By gathering and preprocessing a dataset of noisy speech recordings, the research compares these models based on their recognition accuracy, resilience to different noise types and intensities, and computational efficiency
Keywords: капсульна нейронна мережа; розпызнавання природнього мовлення